Social Participation and Master Plan Public Hearing – myth or truth? (Research, Society and Development, 2021)
This article aims to analyze popular participation about the Urban Development Master Plan (PDDU) of Salvador, Bahia. It is purpose is to correlate the social participation of public hearings in the implementation of the ZEIS instrument with the effects of socio-spatial segregation, analyzing it is complex relationships in space and society. The discussion is focused on the analysis of social positions and space, their impasses in the question of appropriation and in their interactions. In this way, it is possible to investigate the effectiveness of popular participation and the possibilities of restoring the social scene, making evident the problems that involve social movements. The work methodology consists of bibliographic consultations, analysis of official documents (such as the minutes of public hearings held by the City Hall) and interviews with social actors from social organizations and movements that participated in the PDDU discussion.